Effect of straw biochar from different crops on growth and nutrient uptake by peach (Prunus davidiana) seedlings - Liu, Qin; Zhang, Haoran; Wang, Yan; Sun, Jing; Chen, Dong; Tu, Meiyan; Lin, Lijin (Acta physiologiae plantarum, 2022)
The discarding and unreasonable use of straw cause environmental pollution. To improve its utilization, the effects of biochar made from the straws of four crops (rape, rice, wheat, and corn) on the growth and nutrient absorption of peach ( Prunus davidiana ) seedlings were investigated in a pot experiment. The biochar from each crop straw increased the biomass, photosynthetic pigment content, antioxidant enzyme activity and soluble protein content of peach seedlings to some extent. All biochar treatments increased the phosphorus and potassium contents in peach seedlings. The rice and wheat straw biochar increased the nitrogen content in stems and leaves, while the rape and corn straw biochar had a negative effect on the nitrogen content of leaves. Therefore, crop straw biochar can be beneficial for the growth and nutrient absorption by peach seedlings, of which the rape straw biochar shows the best effect.